2007
DOI: 10.1111/j.1600-0870.2007.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal changes in southern hemisphere winter storm track modes

Abstract: A B S T R A C TThe interdecadal changes in southern hemisphere (SH) winter cyclogenesis have been studied using a global twolevel primitive equation instability-model with reanalysed observed July three-dimensional basic states for the periods 1949-1968 and 1975-1994. The early to mid-1970s were a time of quite dramatic reduction in the winter rainfall in the southwest of western Australia (SWWA). We find that the rainfall reduction is associated with a decrease in the vertical mean meridional temperature grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 62 publications
12
99
1
Order By: Relevance
“…The SH zonal wind changes are of hemispheric extension: a decrease in the zonal wind, around 30 • S, with greater intensity in the west Australian jet and South Africa regions, and an increase, around 55 • S, a little southward of the PJ region (Figure 1(f)). These changes are consistent with the findings by Archer and Caldeira (2008), Frederiksen (2005) and Frederiksen and Frederiksen (2007), who also reported, in the SH, a weakening of the subtropical jet, whereas the PJ strengthened after the late 1970s.…”
Section: Jet Streamssupporting
confidence: 82%
See 1 more Smart Citation
“…The SH zonal wind changes are of hemispheric extension: a decrease in the zonal wind, around 30 • S, with greater intensity in the west Australian jet and South Africa regions, and an increase, around 55 • S, a little southward of the PJ region (Figure 1(f)). These changes are consistent with the findings by Archer and Caldeira (2008), Frederiksen (2005) and Frederiksen and Frederiksen (2007), who also reported, in the SH, a weakening of the subtropical jet, whereas the PJ strengthened after the late 1970s.…”
Section: Jet Streamssupporting
confidence: 82%
“…In the Southern Hemisphere (SH), Frederiksen and Frederiksen (2007) found that there were quite large changes in thermal structure and atmospheric circulation, between the periods of 1949-1968 and 1975-1994. Regarding the changes in thermal structure, they found a significant warming of the SH troposphere south of 30 • S in the period [1975][1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994], resulting in a reduction of the Equator-to-pole temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…This result illustrates that a flow pattern with a decreased or southward shift of the zonal mean storm tracks south of Australia is not necessarily detrimental to rainfall in Australia [cf. Karoly (2003); Frederiksen and Frederiksen (2007)]. In this case, the tendency for enhanced blocking promotes cut-off systems in the region that are very efficient at delivering rainfall to the Australian region.…”
Section: Discussionmentioning
confidence: 99%
“…The projected change in the occurrence frequency of strong upper-tropospheric vorticity events may potentially be related to changes in a number of different phenomena, including the closing of the split jet structure over eastern Australia (Grose et al 2012), the position and strength of the subtropical ridge (Timbal and Drosdowsky 2012), atmospheric blocking (Pook et al 2010), Rossby waves (Ndarana and Waugh 2010) and storm tracks (Hoskins andValdes 1990, Frederiksen andFrederiksen 2007). There appears to be a relatively consistent picture of poleward movement emerging from a variety of contrasting methods and phenomena, including the boundary between the…”
Section: Northern Region Southern Region Summer Winter Summer Wintermentioning
confidence: 99%